EVALUASI ALOKASI DANA DESA (ADD) DALAM MENUNJANG PEMBANGUNAN DESA DI KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU (Studi Kasus: Desa Tambusai Utara Tahun 2013-2014) - Aljannah, Siti; Basri, Syafril; Yovita, Indri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the evaluation of village fund allocation, and enabling and inhibiting factors affecting the implementation of the use of the Village Fund Allocation in Village Tambusai Utara, Subdistrict Tambusai Utara, District of Rokan Hulu. This research use primary and secondary data, this research is a descriptif research which analyzed with Logical Framework method used by Bappenas. Analysis based on the method Logical Framework is done, the results showed implementation management of the Village Fund Allocation in support of village of Development in Tambusai Utara. that the Village Fund Allocation obtained Tambusai Utara of village in the 2013 budget of Rp.439.560.000, whereas in 2014 acquire funds (ADD) Rp.375.800.00. The use of the Village Fund Allocation Utara Tambusai is more widely used for fixed income headman and village officials by 45% / Rp.167.800.000 and operational funds for the village of Rp.43.680.000 or around 12%, whereas for the construction of village infrastructure is very small allocation of funds amount of Rp.19.436.000 or around 5%. Factors supporting the implementation the management of the Village Fund Allocation one of which is high original earnings village, which reached Rp.943.745.418. Factors inhibiting the implementation of ADD in the village of Tambusai Utara namely : lack of human resources, both from the village administration has yet professional, and the still weak sub-district and district government guidance so that village empowerment is not maximized.Keywords : Evaluation, Village Fund Allocation, Logical Framework.